Techniques of the World's best Part 6: Setting with Raoul - Kortmann, O. (The Coach, 2000)
A setter has many options of how to trick the opponents blockers. One of these options is shown to us by Raoul Diago (photo). He fakes a setting and then, at the very last instant, pulls away the hand near the net and dinks the ball straight into the opponents half. Mostly the blocker is not ready for that, his arms are not up to block or at least touch the ball. This kind of play is often brought into action after the receiver plays the ball to high or to close to the net and the setter cannot set the ball to his attackers. However this tactical feint is not meant to be a last option. It is best to use it when the receiving of the ball was good and could be set to any of the attackers. In this situation the opponents blockers would be caught unprepared. Don't show your intention to dink the ball until the very last instant. Form your hands as if preparing an overhead pass and take down your right hand as late as possible. Start practicing this in a standing position. You will need many repetitions and constant jumping will tire you out. Play the ball with a quick flick of the wrist and not by moving the forearm as doing a "slam dunk". This gives the impression of a held ball and can cause the referee call a foul. E Dink the ball into the center of the opponents half. This part of the playing-field is the one least guarded. You should always know who is the blocker opposite to you and which tactical formation do the defenders actually take (close or far apart). The setter-feint is a tactical variation, but not magic.